Developmental regulation of the human zeta globin gene in transgenic mice. - Spangler, E A (1990)
We have characterized the expression of the human zeta (zeta) gene, which encodes an embryonic alpha-like globin, in transgenic mice. We find that a 777 base pair fragment spanning erythroid specific hypersensitive site II (HSII) from the distal 5. region of the human beta globin gene cluster potentiates expression of the zeta globin gene. In the absence of the HSII fragment, no zeta expression is observed. Expression of the human zeta gene in mice parallels expression of a murine embryonic alpha-like globin gene (x). Thus, expression of the human zeta gene in mice requires linkage to an erythroid-specific enhancer sequence, but the presence of the enhancer does not affect the developmental regulation of the transgene. Our results indicate that the factors involved in switching from embryonic to adult alpha globin gene expression during development are evolutionarily conserved, and suggest that the transgenic mouse is an in vivo system in which the requirements for the developmental switch in alpha globin gene expression can be analyzed in detail.